Interactions Between the Seasonal and Business Cycles in Production and Inventories - Cecchetti, Stephen G.; Kashyap, Anil K.; Wilcox, David W. (American Economic Review, 1997)
This paper shows that in several U.S. manufacturing industries, the seasonal variability of production and inventories varies with the state of the business cycle. We present a simple model which implies that if firms reduce the seasonal variability of their production as the economy strengthens, and they either hold constant or increase the stock of inventories they bring into the high-production seasons of the year, then they must be facing upward-sloping and convex marginal cost curves. We conclude that firms in a number of industries face upward-sloping and convex marginal-production-cost curves.